THE EVOLUTION OF THE ENERGY SYSTEMS OF UKRAINE AND THE ORGANIZATION OF MANAGEMENT ACCOUNTING IN ENERGY COMPANIES IN CONDITIONS OF RISK - Liubov Gutsalenko; Oleksandr Hutsalenko; Uliana Marchuk; Serhiy Zabolotnyy (Polityki Europejskie, Finanse i Marketing)
An essential prerequisite for the development of Ukraine is a rationally formed energy system that covers the electricity demand of society and assures the smooth functioning of the national economy. The study presents the characteristics of different types of power plants in Ukraine, such as thermal, hydraulic, nuclear, geothermal, and tidal. Furthermore, the share of Ukraine’s contribution to the energy supply of other countries is indicated. Today, the United Energy System of Ukraine is one of Europe’s most significant energy com- plexes with seven regional electric power systems (REES), including Dnipro, Western, Crimean, Southern, Southwestern, Northern, and Central. The research presents the structure of electricity consumption by consumer groups in Ukraine. It indicates the extent of the destruction of Ukraine’s energy capacities by Russia’s invasion. The issue of developing electricity production from alternative energy sources in Ukraine is discussed. Permanent risks and the threat of destruction of energy system objects encourage managers of economic entities to carefully search for quick and accurate problem-solving tools for avoiding critical situations. The accounting system, in particular, management accounting, provides the in- formational component that satisfies the timeliness of providing boards with recommendations on making managerial decisions. The study highlights and describes the stages of implementation of management accounting in energy supply companies in Ukraine. The effectiveness of management accounting in this aspect is emphasized.